2006
DOI: 10.1007/s00586-006-0112-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression in intervertebral disc cells by low and high hydrostatic pressure

Abstract: Intervertebral disc structures are exposed to wide ranges of intradiscal hydrostatic pressure during different loading excercises and are at their minimum during lying or relaxed sitting and at maximum during lifting weights with a round back. We hypothesize that these different loading magnitudes influence the intervertebral disc (IVD) by alteration of disc matrix turnover depending on their magnitudes. Therefore the aim of this study was to assess changes in gene expression of human nucleus cells after the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 20 publications
3
96
0
2
Order By: Relevance
“…Another study using an in vivo rat tail model showed a higher amount of apoptotic cells in the NP when the disc was subjected to dynamic compression of greater than 1.3 MPa [122], whereas 0.9 MPa [122] Response to amplitude modulation: hydrostatic pressure Similar to the findings on axial compression, applying hydrostatic pressure of greater than 2.5 MPa magnitude resulted in a degenerative response of the IVD cells. Decreased anabolic gene expression and increased catabolic gene expression were found on isolated porcine NP cells [31] and AF cells [124], bovine NP cells and human IVD cells [86] using a hydrostatic pressure loading system. Overloading of disc cells even increased the chemokine synthesis, which caused an enhanced migration of endothelial cells [84].…”
Section: Magnitude Response: Axial Compressionmentioning
confidence: 94%
See 2 more Smart Citations
“…Another study using an in vivo rat tail model showed a higher amount of apoptotic cells in the NP when the disc was subjected to dynamic compression of greater than 1.3 MPa [122], whereas 0.9 MPa [122] Response to amplitude modulation: hydrostatic pressure Similar to the findings on axial compression, applying hydrostatic pressure of greater than 2.5 MPa magnitude resulted in a degenerative response of the IVD cells. Decreased anabolic gene expression and increased catabolic gene expression were found on isolated porcine NP cells [31] and AF cells [124], bovine NP cells and human IVD cells [86] using a hydrostatic pressure loading system. Overloading of disc cells even increased the chemokine synthesis, which caused an enhanced migration of endothelial cells [84].…”
Section: Magnitude Response: Axial Compressionmentioning
confidence: 94%
“…It was suggested that cyclic compression at a moderate level simulates physical activities and that this physiological loading might be able to promote repair or postpone disc degeneration. The duration response of IHP on the IVD cells has not been specifically reported in the literature, but an increased anabolic gene expression by human disc cells was demonstrated either after a single 30-min loading [86] or 30-min daily for 4 weeks [85].…”
Section: Time Responsementioning
confidence: 94%
See 1 more Smart Citation
“…These include the presence of growth factors, changes in local biomechanical stresses and in the osmotic environment of the disc cell [44,47,72,98,143,144,157]. Stimulation of endogenous disc cell populations by administered growth factors and other biomimetics in slow delivery carriers within bioscaffolds aim to address some of these questions [53,85].…”
Section: Cell-based Therapies For the Biologic Treatment Of Disc Degementioning
confidence: 99%
“…Material properties of the fibrous scaffold, such as stiffness and permeability, may influence the cellular response to mechanical stimulation. In addition, the osmolarity of the culture medium was not adjusted to approximate conditions found in the disc, which may also modulate the ability of cells to respond to hydrostatic pressurization 14,15,24,25 . In our study, the stated pressure was applied at 0.5 Hz, 4 hours/day, from day 3 of culture to day 14.…”
Section: As Shown Inmentioning
confidence: 99%